Affective Responses and Personal Flourishing - Luigina Mortari (Rosenberg & Sellier, 2016)
The paper reconstructs, develops and discusses Scheler’s Bildung theory to highlight its relevance for educational philosophy. First, we point out that a personality flourishes through a process of progressive individuation which is modulated by affective maturation and promoted by the encounter with an exemplarity. Then, in order to avoid some limits of Scheler’s realism, we suggest rethinking these theses in the light of a new epistemological position (relational enactivism).